Selective laser trabeculoplasty: An updated narrative review - Narayanaswamy, Arun; Sood, Shana R; Thakur, Sahil (Indian journal of ophthalmology, 2024)
Selective laser trabeculoplasty (SLT) has experienced a resurgence in interest, primarily driven by promising findings from the Laser in Glaucoma and Ocular Hypertension Trial. By offering SLT as an initial drug-free treatment option, we may be able to thwart issues such as adherence and persistence that plague our current medical management protocols. In this comprehensive narrative review, we delve into the current body of literature that explores the utility of SLT across a wide spectrum of scenarios and glaucoma subtypes. We present evidence that provides valuable insight into the efficacy and benefits of SLT, positioning it as a viable option in the management of glaucoma. Careful consideration of the associated risks and challenges is also necessary for successful adoption into clinical practice. Despite the ample evidence supporting SLT's efficacy, some questions remain regarding its long-term effects and the potential need for retreatment. This review aims to shed light on these aspects to guide clinicians in making informed decisions and tailoring treatment plans to individual patient needs. This review also provides the readers with a bird's eye view of the potential impact of SLT and adds clarity to the various therapeutic protocols that one can follow to ensure optimal clinical outcomes for our patients.